Isolated Pulmonary Valve Endocarditis Complicated With Septic Emboli to the Lung Causing Pneumothorax, Pneumonia, and Sepsis in an Intravenous Drug Abuser - Swaminath, Deephak (J Investig Med High Impact Case Rep, 2013)
Intravenous drug users are at increased risk for developing right-sided infective endocarditis involving the tricuspid and pulmonary valves. Isolated pulmonary valve endocarditis in intravenous drug users is very rare, and these patients often have more complications, such as pulmonary embolism, sepsis, and pneumonia. We report a case with pulmonary valve endocarditis and extensive pulmonary complications, including sepsis, septic emboli, pneumonia, and pneumothorax. Early identification of pulmonic valve endocarditis and treatment with appropriate antibiotics with or without surgical management should provide better outcomes, and clinicians need to think about pulmonary valve endocarditis in patients with complex respiratory presentations.